Estimation of Consumers’ Willingness to Pay For Cavendish Banana Using Contingent Valuation Method in Special Province Yogyakarta - Novia Dewi Karisyawati; Any Suryantini; Arini Wahyu Utami (Agro Ekonomi, 2019)
Banana is a fruit with the highest consumption level in Indonesia. There are many types of bananas in Indonesia, but only a few types are sold in modern markets and fruit shops, among other Cavendish banana. The Cavendish is known to consumers by their attractive appearance, superior quality and relatively higher prices. This study aims to assess the value of the consumers’ willingness to pay (WTP) for Cavendish banana and its determinant factors. There are two methods used, i.e., contingent valuation method to evaluate the consumers’ willingness to pay, and multiple regression to analyse its determinant factors. Primary data were obtained from 100 respondents by purposive sampling and interviewed in Yogyakarta Special Region between April and June 2019. The results indicate that the consumers’ willingness to pay (WTP) for Cavendish banana is IDR 24,485/kg, which is above the market price. The determinant factors of the consumers’ willingness to pay include the Cavendish banana price, quality of the Cavendish, monthly frequency of consuming banana, family size, income and marital status. The high value of the consumers’ willingness to pay indicates the good opportunity to expand the Cavendish banana market in Special Province Yogyakarta, by taking into account quality and market segmentation.